# If the AM of two positive numbers be three times their geometric mean then the ratio of the numbers is

This question has multiple correct options

A.$3\pm 2\sqrt{2}$

B.$\sqrt{2}\pm 1$

C$17+12\sqrt{2}$

D.${{(3-2\sqrt{2})}^{-2}}$

Answer

Verified

360.9k+ views

Hint: We can assume the numbers to be x and y and proceed to form equations so that we can find the desired result. For that we need to remember the formula of AM and GM i.e. arithmetic mean and geometric mean.

Complete step by step answer:

The formula for finding arithmetic mean of two numbers ‘a’ and ‘b’ is $\dfrac{a+b}{2}$

And the formula for calculating geometric mean of two numbers ‘a’ and ‘b’ is $\sqrt{a\cdot b}$

Let us assume that the two positive numbers are ‘x’ and ‘y’.

Their arithmetic mean is given by- $AM=\dfrac{x+y}{2}$ …(i)

Their geometric mean is given by- $GM=\sqrt{x\cdot y}$ …(ii)

From the question we are given that, AM of x and y is equal to 3 times GM of x and y which implies

$AM=3\cdot GM$

Substituting the value of AM and GM from equation (i) and (ii) we have,

\[\begin{align}

& \dfrac{x+y}{2}=3\sqrt{xy} \\

& \Rightarrow x+y=6\sqrt{xy} \\

\end{align}\]

Dividing both sides by $\sqrt{xy}$ we have,

$\begin{align}

& \dfrac{x+y}{\sqrt{xy}}=6 \\

& \Rightarrow \dfrac{x}{\sqrt{xy}}+\dfrac{y}{\sqrt{xy}}=6 \\

\end{align}$

On simplifying we get,

$\sqrt{\dfrac{x}{y}}+\sqrt{\dfrac{y}{x}}=6$ …(iii)

Now our question was asking us to find the ratio of x and y. Therefore we need to find $x:y\Rightarrow \dfrac{x}{y}$ .

Now let us assume $\dfrac{x}{y}=t$ .

Substituting t in place of $\dfrac{x}{y}$ in equation (iii) we have,

$\sqrt{t}+\sqrt{\dfrac{1}{t}}=6$

On simplifying we get,

$\begin{align}

& \dfrac{\sqrt{t}\cdot \sqrt{t}+\sqrt{1}}{\sqrt{t}}=6 \\

& \Rightarrow \dfrac{t+1}{\sqrt{t}}=6 \\

\end{align}$

Multiplying $\sqrt{t}$ both sides we get,

$\begin{align}

& t+1=6\sqrt{t} \\

& \Rightarrow t-6\sqrt{t}+1=0 \\

\end{align}$

Now we need to solve this equation to get ‘t’.

If we assume $t={{p}^{2}}$ and substitute in the above equation we will have a quadratic equation which we can solve easily.

After substituting ‘t’ we get,

${{p}^{2}}-6p+1=0$

We use the formula $\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$ to find roots of the above quadratic equation where a is coefficient of ${{x}^{2}}$ , b is coefficient of x and c is the constant term.

We have, a=1, b=-6 and c=1

Substituting these values in the above equation we get,

$\begin{align}

& p=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a} \\

& \Rightarrow p=\dfrac{-(-6)\pm \sqrt{{{(-6)}^{2}}-4\cdot 1\cdot 1}}{2\cdot 1} \\

\end{align}$

On simplifying we get,

$\begin{align}

& p=\dfrac{6\pm \sqrt{36-4}}{2} \\

& \Rightarrow p=\dfrac{6\pm \sqrt{32}}{2} \\

& \Rightarrow p=\dfrac{6\pm 4\sqrt{2}}{2} \\

& \Rightarrow p=3\pm 2\sqrt{2} \\

\end{align}$

We had, $t={{p}^{2}}$

Therefore, $t={{(3\pm 2\sqrt{2})}^{2}}$

On squaring we get,

$\begin{align}

& t={{3}^{2}}+{{(2\sqrt{2})}^{2}}\pm 2\cdot 3\cdot 2\sqrt{12} \\

& \Rightarrow t=9+8\pm 12\sqrt{12} \\

& \Rightarrow t=17\pm 12\sqrt{12} \\

\end{align}$

Therefore, $t=\dfrac{x}{y}=17\pm 12\sqrt{12}$

Hence, the answer is option (c).

Note: To find the ratio we may think that we separately need to find x and y but for that we would need two equations to find two variables. We only had one equation so we converted it into one variable and we were able to directly find the ratio without actually knowing the value of x and y.

Complete step by step answer:

The formula for finding arithmetic mean of two numbers ‘a’ and ‘b’ is $\dfrac{a+b}{2}$

And the formula for calculating geometric mean of two numbers ‘a’ and ‘b’ is $\sqrt{a\cdot b}$

Let us assume that the two positive numbers are ‘x’ and ‘y’.

Their arithmetic mean is given by- $AM=\dfrac{x+y}{2}$ …(i)

Their geometric mean is given by- $GM=\sqrt{x\cdot y}$ …(ii)

From the question we are given that, AM of x and y is equal to 3 times GM of x and y which implies

$AM=3\cdot GM$

Substituting the value of AM and GM from equation (i) and (ii) we have,

\[\begin{align}

& \dfrac{x+y}{2}=3\sqrt{xy} \\

& \Rightarrow x+y=6\sqrt{xy} \\

\end{align}\]

Dividing both sides by $\sqrt{xy}$ we have,

$\begin{align}

& \dfrac{x+y}{\sqrt{xy}}=6 \\

& \Rightarrow \dfrac{x}{\sqrt{xy}}+\dfrac{y}{\sqrt{xy}}=6 \\

\end{align}$

On simplifying we get,

$\sqrt{\dfrac{x}{y}}+\sqrt{\dfrac{y}{x}}=6$ …(iii)

Now our question was asking us to find the ratio of x and y. Therefore we need to find $x:y\Rightarrow \dfrac{x}{y}$ .

Now let us assume $\dfrac{x}{y}=t$ .

Substituting t in place of $\dfrac{x}{y}$ in equation (iii) we have,

$\sqrt{t}+\sqrt{\dfrac{1}{t}}=6$

On simplifying we get,

$\begin{align}

& \dfrac{\sqrt{t}\cdot \sqrt{t}+\sqrt{1}}{\sqrt{t}}=6 \\

& \Rightarrow \dfrac{t+1}{\sqrt{t}}=6 \\

\end{align}$

Multiplying $\sqrt{t}$ both sides we get,

$\begin{align}

& t+1=6\sqrt{t} \\

& \Rightarrow t-6\sqrt{t}+1=0 \\

\end{align}$

Now we need to solve this equation to get ‘t’.

If we assume $t={{p}^{2}}$ and substitute in the above equation we will have a quadratic equation which we can solve easily.

After substituting ‘t’ we get,

${{p}^{2}}-6p+1=0$

We use the formula $\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$ to find roots of the above quadratic equation where a is coefficient of ${{x}^{2}}$ , b is coefficient of x and c is the constant term.

We have, a=1, b=-6 and c=1

Substituting these values in the above equation we get,

$\begin{align}

& p=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a} \\

& \Rightarrow p=\dfrac{-(-6)\pm \sqrt{{{(-6)}^{2}}-4\cdot 1\cdot 1}}{2\cdot 1} \\

\end{align}$

On simplifying we get,

$\begin{align}

& p=\dfrac{6\pm \sqrt{36-4}}{2} \\

& \Rightarrow p=\dfrac{6\pm \sqrt{32}}{2} \\

& \Rightarrow p=\dfrac{6\pm 4\sqrt{2}}{2} \\

& \Rightarrow p=3\pm 2\sqrt{2} \\

\end{align}$

We had, $t={{p}^{2}}$

Therefore, $t={{(3\pm 2\sqrt{2})}^{2}}$

On squaring we get,

$\begin{align}

& t={{3}^{2}}+{{(2\sqrt{2})}^{2}}\pm 2\cdot 3\cdot 2\sqrt{12} \\

& \Rightarrow t=9+8\pm 12\sqrt{12} \\

& \Rightarrow t=17\pm 12\sqrt{12} \\

\end{align}$

Therefore, $t=\dfrac{x}{y}=17\pm 12\sqrt{12}$

Hence, the answer is option (c).

Note: To find the ratio we may think that we separately need to find x and y but for that we would need two equations to find two variables. We only had one equation so we converted it into one variable and we were able to directly find the ratio without actually knowing the value of x and y.

Last updated date: 24th Sep 2023

•

Total views: 360.9k

•

Views today: 3.60k

Recently Updated Pages

What do you mean by public facilities

Slogan on Noise Pollution

Paragraph on Friendship

Disadvantages of Advertising

Prepare a Pocket Guide on First Aid for your School

What is the Full Form of ILO, UNICEF and UNESCO

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

The poet says Beauty is heard in Can you hear beauty class 6 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the past tense of read class 10 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE